Increased sensitivity of lymphocytes from patients with systemic autoimmune diseases to DNA alkylation by the methylating carcinogen N-methyl-N-nitrosourea. Issue 6 (June 1988) - Lawley, P D; Topper, R; Denman, A M; Hylton, W; Hill, I D; Harris, G
Abstract : Lymphocytes from patients with various diseases associated with autoimmunity showed both impaired capacity to repair O6-methylguanine (a powerful, promutagenic, directly miscoding base lesion) and increased sensitivity to the cytocidal effects of cellular methylation by N-methyl-N-nitrosourea (MNU) compared with normal controls and patients with other disorders. Defective repair of O6-methylguanine was significantly associated with arthritis and myositis in the group with systemic lupus erythematosus (SLE), and increased sensitivity to the toxic action of MNU was associated with the presence of immune complexes and the administration of steroids to patients with Behçet's syndrome. The results indicate that lymphocytes from patients with the autoimmune diseases studied are more susceptible to DNA damage with possible relevance to aetiopathogenesis.